The runaway bunny - Brown, Margaret Wise 1910-1952.; Hurd, Clement 1908-. (New York HarperCollins, 2005)
A little rabbit who wants to run away tells his mother how he will escape, but she is always right behind him.
Keywords: Rabbits -- Fiction; Mother and child -- Fiction